2004
DOI: 10.1158/1078-0432.ccr-03-0341
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Early- and Late-Relapse Nonseminomatous Germ Cell Tumor and Primitive Neuroectodermal Tumor of the Testis

Abstract: Purpose: To better understand the molecular mechanisms that underlay the development and progression of nonseminomatous germ cell tumor of testis (NSGCTT) as well as malignant transformation of teratoma and primitive neuroectodermal tumor (PNET).Experimental Design: We studied the gene expression profiles of 17 retroperitoneal NSGCTTs (10 yolk sac tumors, 3 embryonal carcinomas, 4 teratomas) and 2 PNETs obtained from patients with two clinical outcomes. Tissue samples were obtained from the Indiana University.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 47 publications
(41 reference statements)
2
32
0
Order By: Relevance
“…Our fi nding on GATA-4 and GATA-6 expression is supported by recent gene expression profi ling in testicular GCTs that showed a 3.9-fold increase in the expression of these markers in YSTs as compared to other types of testicular GCTs [36] . We speculate that the expression of them, especially GATA-6, contributes to the formation of malignant yolk sac endoderm in GCTs.…”
Section: Discussionsupporting
confidence: 81%
“…Our fi nding on GATA-4 and GATA-6 expression is supported by recent gene expression profi ling in testicular GCTs that showed a 3.9-fold increase in the expression of these markers in YSTs as compared to other types of testicular GCTs [36] . We speculate that the expression of them, especially GATA-6, contributes to the formation of malignant yolk sac endoderm in GCTs.…”
Section: Discussionsupporting
confidence: 81%
“…CFLAR has an important role in regulation of apoptosis via the caspase pathway and therefore could be a therapeutic target (Yang, 2008), something that needs further evaluation. In addition, it has been shown that CFLAR can identify GCC patients with cisplatin resistance, based on genomewide expression analysis (Sugimura et al, 2004). Induction of c-FLIP has been reported in EC cell lines, as expected this results in resistance to cisplatin (Spierings et al, 2004).…”
Section: Cisplatin Sensitivity Of Germ Cell Cancersmentioning
confidence: 84%
“…Gene expression profiling approaches have already been applied to the study of underlying transcriptomic alterations in GCTs. However, these studies were mainly performed on a limited number of samples, with only one GCT subtype dominating the whole data set (24,25). In contrast, our analysis was performed on a dataset with a balanced number of seminomas and nonseminomas, which enables more accurate determination of differentially expressed genes across these two groups.…”
Section: Gene Expression Signatures Of Histological Subtypes Of Gctmentioning
confidence: 99%